Estimating the Economic and Social Costs of the Fear of Crime - Dolan, Paul (The British journal of criminology, 2007)
A recent article in this journal, Dolan et al. (2005) provided a methodology for estimating the intangible costs (or losses in quality of life) from violent crime. Here, we develop that methodology to provide estimates of the intangible costs arising from the anticipation of possible victimisation; that is, estimates of the costs of fear of crime. These costs are categorised according to whether they result in non-health losses or health losses. Non-health losses are associated with a) changes in behaviour and/or b) changes in how society is viewed. Possible methods for measuring and valuing these non-health losses are discussed. However, the paper focuses on measuring and providing a provisional monetary valuation for the health losses arising from anticipating crime. [ABSTRACT FROM AUTHOR]